Dynamics of Water Molecules in Concentrated Aqueous Solution of D-Glucose - Chen, Yong-Qiang; Yang, Xiao-Ming (Asian Journal of Chemistry, 2013)
The diffusion coefficient and dipole auto-correlation function of aqueous solution of a-D-glucose and b-D-glucose were investigated in the temperature range of 283-313 K. The results indicate that diffusion coefficient tended to be slightly different with each other between a-D-glucose and b-D-glucose aqueous solution, especially b-D-glucose aqueous solution, which due to different hydrogen bond distribution. Diffusion coefficients were reasonable proportional to the temperature. A clear description about dipole auto-correlation function was given to reveal the diffusion effect of hydrogen bond contribution.